2019
DOI: 10.1126/sciadv.aau4238
|View full text |Cite
|
Sign up to set email alerts
|

A nanofluidic ion regulation membrane with aligned cellulose nanofibers

Abstract: A nanofluidic membrane for ion regulation with aligned cellulose nanofibers was directly obtained from wood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
156
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(173 citation statements)
references
References 37 publications
1
156
0
Order By: Relevance
“…The vibration of carbon-carbon double bonds produces a vibrational band at 1612 cm −1 . The out-of-plane bending vibrations of C─H bonds of aromatic rings lead to a vibrational band at 875 to 750 cm −1 , demonstrating the presence of aromatic rings in the product (18). In addition, the peak at 2925 cm −1 corresponds to the stretching vibration of C─H, demonstrating the presence of aliphatic structures and aromatization during the reaction.…”
Section: Fabrication and Structural Characterization Of Carbon Spheresmentioning
confidence: 97%
See 1 more Smart Citation
“…The vibration of carbon-carbon double bonds produces a vibrational band at 1612 cm −1 . The out-of-plane bending vibrations of C─H bonds of aromatic rings lead to a vibrational band at 875 to 750 cm −1 , demonstrating the presence of aromatic rings in the product (18). In addition, the peak at 2925 cm −1 corresponds to the stretching vibration of C─H, demonstrating the presence of aliphatic structures and aromatization during the reaction.…”
Section: Fabrication and Structural Characterization Of Carbon Spheresmentioning
confidence: 97%
“…The crystalline or amorphous structure of the cellulose and carbon spheres was investigated by x-ray diffraction (XRD) analysis (18,19). Figure 3B shows the XRD patterns of cellulose and carbon spheres obtained from optimal conditions.…”
Section: Fabrication and Structural Characterization Of Carbon Spheresmentioning
confidence: 99%
“…The electrodes, however, showed almost a vertical rise in the imaginary impedance at low frequencies indicating the facile accessibility of electrolyte's ions to charge storage sites on the surface of titanium carbide layers. CNFs act as spacers in between MXene layers and improve the proton transport in the nanocomposite electrode . We compared the capacitive response of the nanocomposite electrodes to that of pristine MXene electrodes by considering a power‐law relationship between the peak current ( i p ) and scan rate ( v ), ( i p = av b ) .…”
Section: Physical Properties Of Ti3c2tx Mxene Ti3c2tx/cnf and Cnf Pmentioning
confidence: 99%
“…[6] In preparation of these wood-based materials, delignification is an essential pretreatment step to extract lignin and partial hemicellulose, aiming to remove the chromophores, and to increase the cell wall accessibility/porosity. Further treatments such as alkaline extraction, [4] acetylation, [7] oxidation, [8,9] could be employed to control the nanostructure and surface chemistry of the delignified wood. However, although the porosity of delignified wood could reach up to 98% when low density wood species is used, typical specific surface area (SSA) for delignified wood prepared by sodium chlorite or peracetic acid delignification was between 20-41 m 2 g −1 .…”
Section: Doi: 101002/adma202003653mentioning
confidence: 99%
“…These wood-based materials have demonstrated pulp fibers were further deprotonated by sodium hydroxide to obtain enhanced tensile strength, transparency while the dewatering time was minimized to 10 s. [20] But no improvement in material properties could be concluded from the nanostructured pulp fibers as compared to CNF-based materials as the structural advantages of wood cell wall structure were lost during pulping. Li et al [8,9] have reported the oxidation of delignified wood in TEMPO/NaClO/NaBr system at pH 10 to prepare nanofluidic cellulosic membrane. The slightly increased charge density in cellulose membrane created 2-20 nm channels between cellulose microfibrils for ion regulation.…”
Section: Doi: 101002/adma202003653mentioning
confidence: 99%